Coarsening behaviour and interfacial structure of γ′ precipitates in Co-Al-W based superalloys. (November 2016) - Vorontsov, V.A.; Barnard, J.S.; Rahman, K.M.; Yan, H.-Y.; Midgley, P.A.; Dye, D.
Abstract: This work discusses the effects of alloying on the coarsening behaviour of the L12 ordered γ ′ phase and the structure of the γ / γ ′ interfaces in three Co-Al-W base superalloys aged at ∼90 °C below the respective solvus temperatures: Co-7Al-7W, Co-10Al-5W-2Ta and Co-7Al-7W-20Ni (at.%). The coarsening kinetics are adequately characterised by the classical Lifshitz-Slyozov-Wagner model for Ostwald ripening. Co-7Al-7W exhibited much slower coarsening than its quaternary derivatives. Alloying can be exploited to modify the coarsening kinetics either by increasing the solvus temperature by adding tantalum, or by adding nickel to shift the rate controlling mechanism towards dependence on the diffusion of aluminium rather than tungsten. Lattice resolution STEM imaging was used to measure the widths of the order-disorder (structural) and Z-contrast (compositional) gradients across the γ / γ ′ interfaces. Similarly to nickel base superalloys, the compositional gradient was found to be wider than the structural. Co-7Al-7W-20Ni had much wider interface gradients than Co-7Al-7W and Co-10Al-5W-2Ta, which suggests that its γ ′ phase stoichiometry is less constrained. A possible correlation between temperature and misfit normalised r vs. t 1/3 coarsening rate coefficients and the structural gradient width has also been identified, whereby alloys with wider interfaces exhibit faster coarsening rates. Graphical abstract: